The Fragile Brain: Stress Vulnerability, Negative Affect and GABAergic Neurocircuits in Psychosis. (31st May 2019) - Taylor, Stephan F; Grove, Tyler B; Ellingrod, Vicki L; Tso, Ivy F
Abstract: Persons with schizophrenia exhibit sensitivity to stress and negative affect (NA), both strongly correlated with poor functional outcome. This theoretical review suggests that NA reflects a "fragile brain, " ie, vulnerable to stress, including events not experienced as stressful by healthy individuals. Based on postmortem evidence of altered gamma-aminobutyric acid (GABA) function in parvalbumin positive interneurons (PVI), animal models of PVI abnormalities and neuroimaging data with GABAergic challenge, it is suggested that GABAergic disruptions weaken cortical regions, which leads to stress vulnerability and excessive NA. Neurocircuits that respond to stressful and salient environmental stimuli, such as the hypothalamic-pituitary-adrenal axis and the amygdala, are highly dysregulated in schizophrenia, exhibiting hypo- and hyper-activity. PVI abnormalities in lateral prefrontal cortex and hippocampus have been hypothesized to affect cognitive function and positive symptoms, respectively; in the medial frontal cortex (dorsal anterior cingulate cortex and dorsal medial prefrontal cortex), these abnormalities may lead to vulnerability to stress, NA and dysregulation of stress responsive systems. Given that postmortem PVI disruptions have been identified in other conditions, such as bipolar disorder and autism, stress vulnerability may reflect a transdiagnostic dimension of psychopathology.